KONSTRUKSI SANKSI ADMINISTRATIF PERATURAN DAERAH PROVINSI BALI NOMOR 2 TAHUN 2012 - Kadek Putra Arik Persona (University of Udayana, 2015)
The study describes the overlap of arrangements of administrative sanctions in the Law No. 12 of 2011 with the construction of administrative sanctions in the Local Regulation of Bali Province No. 2 of 2012. The arrangements of administrative sanctions according to Law No. 12 of 2011 are stipulated in appendix II number 64 which stipulates that the substance in the form of administrative sanctions or civil sanctions for the violation of these norms are formulated into one part (chapter) with the norms that impose administrative sanctions or civil sanctions, and in appendix II number 65 which regulates if there is more than one norm that provides administrative or civil sanctions, administrative sanctions or civil sanctions are formulated in the last chapter of the section. Thus, it does not formulate the provision of sanctions that also contains criminal sanctions, civil penalties and administrative sanctions in one chapter. The arrangements of administrative sanctions in the Local Regulation of Bali Province No. 2 of 2012 are stipulated in Chapter XIV of Article 33 paragraph (1), (2), and (3), thus it is contrary to the provisions of Appendix II of Law of the Republic of Indonesia Number 12 of 2011 numbers 64 and 65.